The Impact of Digital Literacy and Achievement Motivation on Employee Performance: The Mediating Role of Innovative Behavior in the Communication and Information Office of Pasuruan Regency - Sari, Rivamawati Milla; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The rapid advancement of digital technologies has reshaped organizational operations and demands employees to master evolving systems while maintaining effective performance. This study examines the influence of digital literacy and achievement motivation on employee performance, with innovative behavior as a mediating factor, at the Communication and Information Office of Pasuruan Regency. A quantitative explanatory approach was applied, involving all 65 employees as respondents through structured questionnaires, supported by observations and interviews to strengthen data accuracy. Data were processed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both the measurement and structural models. The findings reveal that digital literacy significantly enhances employee performance by improving information processing abilities, technological adaptability, and the effective use of digital platforms to support work completion. Achievement motivation also shows a positive effect on performance, reflecting the role of personal initiative and goal-oriented behavior. Among the tested variables, innovative behavior demonstrates the strongest impact on performance, indicating that creativity, willingness to innovate, and problem-solving capabilities are essential for achieving optimal results. Furthermore, digital literacy and achievement motivation indirectly influence performance through innovative behavior, confirming its mediating role in the model. These results highlight the importance of continuous digital competency development, motivation enhancement through recognition and fair evaluation, and the creation of a supportive climate for innovation. Future research may explore additional contextual factors such as leadership style or work environment to enrich understanding of performance improvement in digitally oriented public institutions.